Dynamics of yoga [2nd ed.] the foundations of Bihar yoga - Saraswati, Swami Satyananda (Munger Yoga Publications Trust, 2002)
Dynamic of Yoga outlines the original yogic concepts and practices which form the foundations of Bihar Yoga, or Satyananda Yoga. Ideal as an introduction to Bihar Yoga, these early teaching of Swami Satyananda Saraswati aim to give the reader a deeper understanding of yoga and its practical application in daily life. The core practices of yoga and meditation are highlighted, with emphasis on mind management and the development of awareness. The book remains a timeless work on the art and science of yoga as seen through the eyes of a master. Include in this edition is a new chapter outlining the history and development of Bihar Yoga.
Keywords: Yoga